Biomimetic Microsensors Inspired by Marine Life - Kottapalli, Ajay Giri Prakash; Asadnia, Mohsen; Miao, Jianmin; Triantafyllou, Michael S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book narrates the development of various biomimetic microelectromechanical systems (MEMS) sensors, such as pressure, flow, acceleration, chemical, and tactile sensors, that are inspired by sensing phenomenon that exist in marine life. The research described in this book is multi-faceted and combines the expertise and understanding from diverse fields, including biomimetics, microfabrication, sensor engineering, MEMS design, nanotechnology, and material science. A series of chapters examine the design and fabrication of MEMS sensors that function on piezoresistive, piezoelectric, strain gauge, and chemical sensing principles. By translating nature-based engineering solutions to artificial manmade technology, we could find innovative solutions to critical problems.
Lateral-Line Inspired MEMS Neuromast Sensors -- Biological Olfaction Inspired Chemical Sensors -- Bio-inspired Underwater Active and Passive Sensing -- Sensing on Robots Inspired by Nature.
Keywords: Microtechnology; Microelectromechanical systems; Biotechnology; Control engineering; Robotics; Automation; Biomedical engineering; Biomaterials; Microsystems and MEMS; Biotechnology; Control, Robotics, Automation; Biomedical Engineering and Bioengineering; Biomaterials